Pahiatua borough : the formative years (1881-1892) : a thesis presented in partial fufilment of the requirements for the degree of Master of Arts in History at Massey University - Bentley, Byron John (Massey University, 1973)
To the New Zealand citizen of the 1970's, surrounded either by the tall buildings of an urban landscape, or the predominantly open fields of a rural environment, the terms Seventy and Forty mile bush may connote more of a legendary forest tract, than the actual existence, less than 100 years ago, of a vast primeval forest, extending from Norsewood to Mauriceville, on the eastern side of the Tararua and Ruahine ranges in the North Island of New Zealand. The fact that nowadays, dairy and sheepfarms and the towns of Dannevirke, Woodville, Pahiatua and Eketahuna cover what was once bushland, is illustrative of how quickly the early inhabitants of the area adapted to their new environment, and turned their vision of viable communities surrounded by farmland into reality. This making over of the accessible parts of the North Island inland forest was the outstanding achievement of our people .... The achievements of all these ordinary struggling people makes the really significant history of the North Island. George Jobberns 1 1. Quoted in S.H. Franklin "The Village and the Bush", from J. Forster (ed.) "Social Processes in New Zealand", p.102. The story of Pahiatua is part of "this making over of the accessible parts of the North Island inland forest", though in many ways it is a unique variation on this theme.
Keywords: Pahiatua (N.Z.); History